Systems Engineering roles to handle emergent properties and behaviors in complex technical systems - Gräßler, Iris; Pfeifer, Jan Niklas; Hintz, Florian; Meyrl, Nicolas (INCOSE International Symposium)
Abstract Engineering projects for complex technical systems such as automobiles demand extensive requirement specifications and corresponding hierarchy levels in system architectures. Especially when considering emergent phenomena, such as total weight or aerodynamics, a closely networked collaboration of discipline‐specific and cross‐disciplinary roles is required. Further, in large organizations with a group structure, resulting functional and non‐functional contents need to be managed by distinct Systems Engineering roles. For example, the role “property manager” takes care of achieving overarching product properties, such as weight or aerodynamics, which cannot be directly fixed, but result from many specifications. This paper proposes new Systems Engineering roles and their application in a German Original Equipment Manufacturer (OEM). For validation, the roles have already been applied in everyday engineering projects at the OEM. The concept proved to be indispensable and transferable to other Systems Engineering projects.
Keywords: Systems Engineering roles; properties; features; emergent phenomena; automotive

Wissenschaftsdidaktik als kritische Kommunikationsanalyse
Welchen Zusammenhang haben Kommunikation, Lehre und Wissenschaft? Die Autor*innen denken Ludwig Hubers Idee von Wissenschaftsdidaktik als Analyse der Kommunikation von Wissenschaften weiter. In deskriptiv-kritischer Absicht wird Kommunikation von konkreten Wissenschaften im Kontext der Lehre – spezifischen Lehrtexten, in der Lehre genutzten Forschungstexten und fachlichen Diskursen über Lehre – zum Gegenstand hochschuldidaktischer Beobachtung und Analyse. Die Beiträge aus verschiedenen Disziplinen regen zur kritischen Hinterfragung wissenschaftlicher Praxis an und eröffnen Wissenschaften die Möglichkeit, sich durch die kritische Selbstreflexion ihrer Kommunikation weiterzuentwickeln. Beteiligte Disziplinen sind Biologie, Chemie, Erziehungswissenschaft, Ethik, Geographie, Geschichtswissenschaft, Literaturwissenschaft, Mathematik, Medizin, Physik, Psychologie und Volkswirtschaftslehre.

Empathie und Einstellungen von Grundschulkindern gegenüber Peers mit emotional-sozialem Förderbedarf. Vortrag auf der Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF). Thema: „Wissenstransfer zwischen Bildungsforschung, Bildungspraxis und Lehrer*innenbildung“. - Löper, Marwin Felix; Hellmich, Frank

Feedback als Prädiktor für die Motivation und Mathematikleistung von Grundschulkindern. Vortrag auf der Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF). Thema: „Wissenstransfer zwischen Bildungsforschung, Bildungspraxis und Lehrer*innenbildung“. - Finke, Nils; Hellmich, Frank

Erfassung affektiver Reaktionen bei moderater körperlich-sportlicher Aktivität und Entspannungsverfahren. Eine Validierungsstudie der Feeling Scale und der Felt Arousal Scale - Thorenz, Kristin
Die Entscheidung, den eigenen Lebensstil zu verändern und körperlich-sportliche Aktivitäten zu implementieren, geht über rationale Prozesse hinaus. Das Wissen um die Förderung der individuellen physischen Gesundheit durch körperlich-sportliche Aktivität reicht nicht aus, um bewegungsinaktive Personen an körperlich-sportliche Aktivitäten zu binden. Die Erfahrung sich während oder nach einer Aktivität gut zu fühlen, steigert die Motivation diese Aktivität zu wiederholen. Die Wahrnehmung des aktuellen psychischen Befindens in Bezug auf eine körperlich-sportliche Aktivität beeinflusst folglich zukünftiges Bewegungsverhalten. Das aktuelle psychische Befinden kann über die Dimensionen affektive Valenz und Aktiviertheit erfasst werden. Im anglo-amerikanischen Raum werden die Feeling Scale (FS) und die Felt Arousal Scale (FAS) als Messinstrumente zur Erfassung dieser Dimensionen bereits eingesetzt. Das Ziel des vorliegenden Promotionsprojektes liegt darin, die deutsche Übersetzung der FS und der FAS für die drei Interventionsformen moderates Joggen, Progressive Muskelrelaxation sowie Auto-genes Training zu validieren. Die Dimensionen affektive Valenz und Aktiviertheit wurden jeweils direkt vor und nach der Interventionsdurchführung mit der FS und der FAS erfasst. Zur Validitätsprüfung wurde der Self-Assessment Manikin als ein weiteres Messinstrument erhoben. Die Gültigkeit der FS und der FAS konnte mit den Multitrait-Multimethod Analysen für alle drei Interventionsformen bestätigt werden. Im Ergebnis stehen Forscherinnen und Forschern des deutschen Sprachraums zwei valide Messinstrumente zur Erfassung der affektiven Valenz und Aktiviertheit für verschiedene Anwendungsbereiche zur Verfügung.

The Affective Responses to Moderate Physical Activity: A Further Study to Prove the Convergent and the Discriminant Validity for the German Versions of the Feeling Scale and the Felt Arousal Scale - Thorenz, Kristin; Sudeck, Gorden; Berwinkel, Andre; Weigelt, Matthias (Behavioral Sciences)
The present study proves the construct validity of the German versions of the Feeling Scale (FS) and the Felt Arousal Scale (FAS) for measuring the affective responses (affective valence and arousal) for a moderate-intensity jogging (JG) exercise. In previous studies, both scales were validated for a high-intensity bicycle ergometer exercise and for relaxation techniques. In the present study, 194 participants performed the JG exercise for 45 min and completed the FS and the FAS, as well as the Self-Assessment Manikin (SAM), for a self–other comparison in a pre-test-intervention-post-test design. The results of the correlation analyses replicated the previous findings for the high-intensity bicycle ergometer exercise and the relaxation techniques, revealing significant positive correlations for the valence dimension between the FS and the SAM-Pleasure subscale (r = 0.50) and for the arousal dimension between the FAS and the SAM-Arousal subscale (r = 0.16). These findings suggest that the German versions of the FS and the FAS are also suitable for exercises of moderate intensity.

The affective responses to moderate physical activity: A further validation study for the German versions of the Feeling Scale and the Felt Arousal Scale - Thorenz, Kristin; Sudeck, Gorden; Berwinkel, Andre; Weigelt, Matthias (Methodenvielfalt: Lebendigkeit in Theorie und Praxis Abstractband zur 56. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (ASP))

Mehrsprachigkeit in der Schule. Sprachbildung im und durch Sachunterricht.

Umsetzung und Ergebnisse des Projekts „PROCARE-Prävention in stationären Pflegeeinrichtungen“ in Paderborn - Thorenz, Kristin; Berwinkel, Andre; Pietschmann, Juliane; Joellenbeck, Thomas; Weigelt, Matthias

Dorffunk. Kommunikation auf dem Land in Juli Zehs Dorfromanen Unterleuten und Über Menschen - Leineweber, Jonas (Rheinisch-westfälische Zeitschrift für Volkskunde)

Manifolds of absolutely continuous functions with values in an infinite-dimensional manifold and regularity properties of half-Lie groups - Pinaud, Matthieu

Rezension zu: Daniel Drascek, Helmut Groschwitz, Gabriele Wolf (Hg.): Kulturerbe als kulturelle Praxis – Kulturerbe in der Beratungspraxis (Bayrische Schriften zur Volkskunde 12). München 2022 - Leineweber, Jonas (Rheinisch-westfälische Zeitschrift für Volkskunde)

Didaktik der Sozialpädagogik – Entwicklungslinien, Diskurse und Herausforderungen. - Göddertz, Nina (Zeitschrift für Pädagogikunterricht)

Action inhibition in a sport-specific paradigm: examining the limits of action control in basketball - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Psychological Research)
Abstract To investigate the point where inappropriate defensive movements can no longer be inhibited and to validate suitable stimulus material for constructing a basketball-specific anticipation-response-inhibition task, two experiments were conducted. In Experiment 1, participants without basketball expertise (N = 25) watched a video of a basketball jump shot and were asked to release the space bar at the point when the ball leaves the player's fingertips (go-trials). In 25% of all trials, the video was stopped prematurely and participants should withhold their finger-lift response (stop-trials). A staircase-tracking algorithm was used to adjust the point-in-time when the jump shot was stopped in a way that participants’ inhibition rate was at 50% (reflecting the so called “point-of-no-return”, PNR). In Experiment 2, the stimulus material was adapted so that stop-trials simulated a pump fake. The PNR in Experiment 1 was located 187 ms and in Experiment 2 177 ms before the point of ball release. Precision performance benefit from practice across blocks and participants delayed their responses after stop-trials in a subsequent go-trial, which reflects strategic post-stop-trial adjustments. Based on the comparable results of previous studies, the given stimulus material is suitable for investigating response inhibition skills in dynamic sport-specific environments.

Émile Durkheim: Father of the Sociology of Education - Lin-Januszewski, Liang-Wen (The Palgrave Handbook of Educational Thinkers)
The establishment of the sociology of education is attributed to Émile Durkheim, one of the founding fathers of sociology. Durkheim’s fervent commitment to the sociological foundations of research methods and the inherent nature of education distinguish the sociological perspective on education from its counterparts in other social sciences, thereby inaugurating the inception of theoretical paradigms within the field of sociology of education. This chapter delineates the motivational forces behind Durkheim’s exploration of education’s multifaceted functions through the lens of social inquiry. It also discusses Durkheim’s significant contributions to the sociology of education, including innovative sociological methods for investigating educational phenomena and his three prominent books: Education and Sociology, Moral Education, and The Evolution of Educational Thought. New insights derived from Durkheim’s conceptualization of functionalism applied to the study of education are also presented. Concluding this chapter is a contemplative reflection on the unfinished intellectual endeavor of interpreting Durkheim’s work through the conflict tradition. This approach has been consistently overlooked, yet it provides valuable insights and unveils profound explanatory mechanisms for sociological analyses of education.

Das Forschungsprojekt im Spiegel praxistheoretischer inklusionsbezogener Unterrichtsforschung - Schröer, Franz; Reis, Oliver; Kruse, Iris; Rohlfing, Katharina (Inklusion verstehen. Szenen aus dem Unterricht in interdisziplinärer Reflexion)

YouTube-Fitness als exemplarisches Phänomen einer Kultur der Digitalität. Medienkompetenzanalytische Perspektiven auf eine körperfokussierte Lifeloggingpraxis. - Burgfeld-Meise, Bianca; Dehmel, Lukas (Jahrbuch Medienpädagogik 21. Mit Medienpädagogik in die Zukunft.)

LFB-Labs-digital: Schülerlabore als Ort der Lehrkräftefortbildung in der digitalen Welt: Ein Bericht zur Konzeption eines Verbundprojektes - Kirchhoff, Tim; Schwedler, Stefanie; Abels, Simone; Acher, Andres; Anselmetti, Dario; Besa, Kris-Stephen; Biehl, Jonathan; Blumberg, Eva; Breiter, Andreas; Brückmann, Maja; Büntemeyer, Doreen; El Tegani, Mahdi; et al. (PFLB – PraxisForschungLehrer*innenBildung)
Schülerlabore haben unter anderem zum Ziel, die Motivation, insbesondere das Interesse – i.S. einer gegenstandsbezogenen Motivation – von Schüler*innen an MINT-Themen und -Arbeitsweisen zu fördern. Darüber hinaus konnten sie sich schneller und produktiver als die formalen Bildungsorte den Herausforderungen der digitalen Transformation stellen. Das Potenzial, Schülerlabore auch als innovative Orte der Lehrkräftefortbildung (LFB) zu nutzen und digitalisierungsbezogene Kompetenzen bei Lehrkräften aufzubauen, wurde bisher nicht ausgeschöpft. Im Verbundprojekt mit insgesamt acht Standorten werden Schülerlabore zu LFB-Labs-digital ausgebaut und die Frage nach Implementierungsvoraussetzungen gelingender Fortbildungen in der digitalen Welt im MINT-Bereich bearbeitet. In diesem Artikel werden die theoretische Fundierung, Ziele und anvisierten Forschungsarbeiten des Verbunds LFB-Labs-digital dargelegt. Zur Unterstützung der mit der forschungsbasierten Qualitätsentwicklung der MINT-bezogenen Aus-, Fort- und Weiterbildung von Lehrkräften betrauten Einrichtungen in den Ländern sollen in Kooperation mit dem Kompetenzzentrum MINT des Bundes die Lernorte „Schülerlabore“ für die digitale LFB erschlossen werden, um vermittelt hierüber die Motivation von Schüler*innen für die MINT-Fächer zu fördern. Die in den Schülerlaboren evaluierten und vom fächerübergreifenden adaptiven Qualitätsmanagement für die LFB wissenschaftlich begleiteten Good-Practice-Beispiele werden zur Grundlage für den „Referenzrahmen LFB-Labs-digital“. Dieser wird – vor dem Hintergrund einer Ergebnistriangulation aus der Begleitforschung sowie den damit parallelisierten Studien zur Evidenzbasierung der Lehrkräftequalifizierung in der digitalen Welt und dem Musterqualitätshandbuch LFB – entwickelt und von einem Implementierungsbeirat mit ausgewiesenen Expert*innen in diesem Bereich auf Transferoptionen hin geprüft. Die digitale Infrastruktur für die LFB-Labs-digital-Veranstaltungsformate wird hierzu prozessbegleitend ausgebaut.

Disentangling Dialect from Social Bias via Multitask Learning to Improve Fairness - Spliethöver, Maximilian; Menon, Sai Nikhil; Wachsmuth, Henning (Findings of the Association for Computational Linguistics ACL 2024)
Dialects introduce syntactic and lexical variations in language that occur in regional or social groups. Most NLP methods are not sensitive to such variations. This may lead to unfair behavior of the methods, conveying negative bias towards dialect speakers. While previous work has studied dialect-related fairness for aspects like hate speech, other aspects of biased language, such as lewdness, remain fully unexplored. To fill this gap, we investigate performance disparities between dialects in the detection of five aspects of biased language and how to mitigate them. To alleviate bias, we present a multitask learning approach that models dialect language as an auxiliary task to incorporate syntactic and lexical variations. In our experiments with African-American English dialect, we provide empirical evidence that complementing common learning approaches with dialect modeling improves their fairness. Furthermore, the results suggest that multitask learning achieves state-of-the-art performance and helps to detect properties of biased language more reliably.

Artificial Intelligence - Naudé, Wim; Gries, Thomas; Dimitri, Nicola
Is Artificial Intelligence a more significant invention than electricity? Will it result in explosive economic growth and unimaginable wealth for all, or will it cause the extinction of all humans? Artificial Intelligence: Economic Perspectives and Models provides a sober analysis of these questions from an economics perspective. It argues that to better understand the impact of AI on economic outcomes, we must fundamentally change the way we think about AI in relation to models of economic growth. It describes the progress that has been made so far and offers two ways in which current modelling can be improved: firstly, to incorporate the nature of AI as providing abilities that complement and/or substitute for labour, and secondly, to consider demand-side constraints. Outlining the decision-theory basis of both AI and economics, this book shows how this, and the incorporation of AI into economic models, can provide useful tools for safe, human-centered AI.